Meningkatkan Ekowisata Melalui Keterlibatan Masyarakat dan Keberlanjutan Lingkungan: Pembelajaran dari Gunung Muria - Aziz Akbar Mukasyaf; Zidan Wahyu Saputra (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2025)
Mount Muria, located on the border of Kudus, Pati, and Jepara in Central Java Province, holds great potential as an ecotourism destination. Despite limited promotion and exploration, the area offers stunning natural scenery and opportunities for nature-based and religious hiking ecotourism. This study aims to identify the development potential of hiking ecotourism on Mount Muria, specifically at Puncak 29 and Puncak Natas Angin. A quantitative descriptive approach was employed, integrated with a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to formulate development strategies. Data collection was conducted using field observations and in-depth interviews with stakeholders such as local communities, hikers and tourism managers. The SWOT analysis revealed that the main strengths of the two peaks lie in their natural beauty, religious tourism appeal, and biodiversity, while weaknesses include inadequate infrastructure and facilities. Threats such as waste management issues, low environmental awareness, and landslide risks also emerged. The results indicate that both locations fall into the